Cell‐free DNA screening for fetal aneuploidy using the rolling circle method: A step towards non invasive prenatal testing simplification. (7th October 2021) - Pavanello, Enza; Sciarrone, Andrea; Guaraldo, Varvara; Muccinelli, Elisabetta; Ciuffreda, Valentina Pia; Sauro, Pina; Bondielli, Giulia; Mirante, Sandra; Mengozzi, Giulio; Viora, Elsa; Cuckle, Howard; Pasini, Barbara
Abstract: Objective: To assess the efficacy of cell‐free (cf)DNA screening for aneuploidy using the automated system based on rolling circle replication. Methods: A prospective study among women referred for invasive prenatal diagnosis between July 2018 and December 2019. The plasma fraction was extracted within 5 days from blood collection, stored at −20°C and cfDNA measured between January and December 2019. Results: A total of 805 women were recruited; 778 with singleton pregnancies and 27 twins. There were 48 Down syndrome, 25 Edwards syndrome and 3 Patau syndrome cases. Overall, the no‐call rate was 2.6% (95% confidence interval 1.6%–3.9%) which reduced from 4.7% to 1.1% after relocation of the system ( p  < 0.002) to ensure a constant ambient temperature below 25°C. In singletons the Down syndrome detection rate (DR) was 100% (93%–100%) and false‐positive rate (FPR) 0.14% (0.00%–0.79%). The Edwards syndrome DR was 96% (80%–100%) and FPR 0.78% (0.29%–1.7%). One false‐positive had a confined placental trisomy 18 and the remaining five a z‐score requiring sample repetition; all the false‐positives occurred before system relocation ( p  < 0.005). Patau syndrome DR and FPR were 67% (9.4%–99%) and 0.26% (0.03%–0.95%). Conclusion: The cfDNA rolling circle method yields similar results to other methods provided that room temperature is adequately controlled. Key points: What is already known about this topic? Cell‐free DNA has considerably better screening performance than conventional tests Performance of the rolling circle method, in a single study, was similar to the three widely used methods What does this study add? Confirmation of the performance of the rolling circle method Demonstration that it can be readily incorporated into a conventional screening laboratory